The Meaning of the Green Color in the Film Photocopier by Wregas Bhanuteja - Rahmat, Theobaldus Juniardy; Kasmana, Kankan (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
Film is one of the most effective media for communicating information to audiences. Every element used in a film has a specific meaning and function in constructing the message to be conveyed, including the use of color tone in a scene. In cinematography, color tone not only functions as a visual element, but can also represent the mood, emotions, and psychological condition of the characters in the story. This study aims to analyze the meaning of green color tones in the film photocopier and how their use represents the psychological condition of the main character, Suryani. This study uses a qualitative method with a visual analysis approach to several scenes that feature a predominance of green color tones. The analysis was conducted by observing the appearance of color in the visual composition, lighting, and context of the scenes in the film. The results of the study show that green tones create a gloomy atmosphere and emotional pressure, as well as depict the psychological condition of the main character who is in a situation of injustice. Thus, the use of green serves as a visual symbol that reinforces the delivery of emotions and narrative messages in the film.